2008
DOI: 10.1074/jbc.m707416200
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Ester Up-regulates Phospholipase D1 but Not Phospholipase D2 Expression through a PKC/Ras/ERK/NFκB-dependent Pathway and Enhances Matrix Metalloproteinase-9 Secretion in Colon Cancer Cells

Abstract: Despite its importance in cell proliferation and tumorigenesis, very little is known about the molecular mechanism underlying the regulation of phospholipase D (PLD) expression. PLD isozymes are significantly co-overexpressed with cancer marker genes in colorectal carcinoma. Phorbol 12-myristate 13-acetate (PMA) treatment, as a mitogenic signal in colon cancer cells, selectively increases PLD1 expression in transcription and posttranscription. Moreover, experiments using intraperitoneal injection of PMA into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…16 Thus, we tried to determine whether ligands that stimulate PLD activity might induce PLD expression. We confirmed that physiological ligands such as PDGF, EGF or IL-1b stimulated PLD activity in SK-BR3 breast cancer cells (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Thus, we tried to determine whether ligands that stimulate PLD activity might induce PLD expression. We confirmed that physiological ligands such as PDGF, EGF or IL-1b stimulated PLD activity in SK-BR3 breast cancer cells (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16,21 Zones of gelatinolytic activity were detected as clear bands against a blue background. Inverted images are presented.…”
Section: Zymographymentioning
confidence: 99%
See 2 more Smart Citations
“…Both LPA and PA (Fig. 3A) are known to activate the MAPK and PI3K signaling pathways (29)(30)(31), and inhibition of CK in cells was shown to significantly decrease both pAKT and pERK levels (26). However, EDI3 knockdown in MCF-7 cells showed no effect on either pathway (Fig.…”
Section: Edi3 Positively Regulates Cell Migration In Vitro Via Pkcα Smentioning
confidence: 99%